Analysis of cobalt for human sports drug testing purposes using ICP‐ and LC‐ICP‐MS. Issue 11 (16th November 2020) - Knoop, Andre; Planitz, Peter; Wüst, Bernhard; Thevis, Mario
Abstract: Due to the current demands in the fight against manipulation of blood and blood components, commonly referred to as "blood doping" in sports drug testing, specific and sensitive detection methods enabling the detection of prohibited substances and methods of doping are required. Similar to illicit blood transfusions, erythropoiesis stimulating agents have been shown to be misused in sport, aiming at improving an athlete's aerobic capacity and endurance performance. Amongst other strategies, the administration of ionic cobalt (Co 2+ ) can increase the number of erythrocytes by stimulating the endogenous erythropoietin (EPO) biosynthesis. Conversely, several organic Co‐containing compounds such as cyanocobalamin (vitamin B12) are not prohibited in sports, and thus, an analytical differentiation of permitted and banned contributions to urinary Co‐concentrations is desirable. An excretion study with daily applications of either 1 mg of CoCl2 or 1 mg of cyanocobalamin was conducted with 20 volunteers over a period of 14 consecutive days. Urine, plasma, and concentrated red blood cells were analyzed for their cobalt content. The samples were collected starting 7 days before the administration until 7 days after. Total Co concentrations were analyzed by using inductively coupled plasma mass spectrometry (ICP‐MS), which yielded significantly elevated levels exclusively after inorganic cobalt intake. Furthermore, a liquid chromatography (LC)‐ICP‐MS approach was established and employed for the simultaneous determination of organically bound and inorganic cobalt by chromatographic separation within one single run. The analytical approach offers the option to further develop detection methods of illegal Co 2+ supplementation in sport. Abstract : Aa, an erythropoiesis activating agent inorganic cobalt, is banned as a doping substance in elite sports. By means of (LC‐) ICP‐MS approaches, analytical detection in different body fluids and its discrimination against legitimate presence of organic cyanocobalamin (vitamin B12) were evaluated within an excretion study.